Coordination contracts for a supply chain with yield uncertainty and low-carbon preference. (20th December 2018) - Peng, Hongjun; Pang, Tao; Cong, Jing
Abstract: We consider a supply chain consisting of a supplier and a manufacturer under the carbon emission cap-and-trade scheme, where the manufacturer faces yield uncertainty. A Stackelberg model is adopted to investigate the production, price and carbon emission reduction decisions for the decentralized and centralized supply chain. We analyze the popular quantity discount contract and the revenue sharing contract for the supply chain. Our results indicate that the quantity discount contract can efficiently coordinate the low-carbon supply chain, but the revenue-sharing contract cannot. We then design a new contract of revenue-sharing with subsidy on emission reduction (RSS) to coordinate the supply chain. We have showed that the proposed RSS contract can coordinate the low-carbon supply chain with yield uncertainty perfectly and the carbon emission reduction level can achieve the level under the centralized case. Highlights: Integrate yield uncertainty and consumers' low-carbon preference for a low-carbon supply chain. The quantity discount contract can coordinate the low-carbon supply chain perfectly. The revenue-sharing contract cannot coordinate the low-carbon supply chain efficiently. We propose a revenue-sharing with subsidy on emission reduction (RSS) contract. The RSS contract can perfectly coordinate the supply chain and reduce the carbon emission.